An Interview with Edsger W. Dijkstra. - Misa, Thomas J. (Communications of the ACM, 2010)
The article presents an interview with computer programmer Edsger W. Dijkstra. Dijkstra comments on how he left the Netherlands to study computer programming in Cambridge, England and how he developed an algorithm to find the shortest distance between two points as a way of demonstrating the Automatic Calculator Mathematical Centre (ARMAC) system. He comments on how multilingualism is useful in computer programming.